The Rise of the Second Dominant Party System in India: BJP's New Social Coalition in 2019. (December 2019) - Chhibber, Pradeep; Verma, Rahul
The social coalition that supported the Bharatiya Janata Party in 2019 mirrored the demographic profile of the Hindu society. The party made substantial gains among the lower castes, the poor, rural voters, and less educated. How did BJP manage to attract these new voters? We argue that the immediate context of 2019 elections along with a profound ideological shift in Indian politics lies at the heart of the BJP's success. Underpinning the short-term factors of Modi's popularity, BJP's organizational advantage, heightened nationalistic sentiments, and expansive welfare politics, a new form of ethno-political majoritarianism delinked from religious Hindu nationalism was key to the party's ability to attract new voters.